Ossification of the anterior longitudinal ligament observed during upper endoscopy for dysphagia. Issue 2 (22nd July 2016) - Yonenaga, Kazumichi; Maita, Hiroki; Yonehara, Yoshiyuki; Namaki, Shunsuke; Suenaga, Hideyuki; Takato, Tsuyoshi
Abstract: The patient was a 78‐year‐old man with a chief complaint of dysphagia. Extrinsic displacement of the posterior hypopharyngeal wall was observed on upper endoscopy. The patient was diagnosed with ossification of the anterior longitudinal ligament (OALL) of the cervical spine according to lateral cervical spine radiographic findings. The OALL caused dysphagia. In swallowing endoscopic assessments of patients with dysphagia, OALL of the cervical spine should be differentiated from other possible diagnoses by using radiography when extrinsic displacement of the posterior oropharyngeal or hypopharyngeal wall is observed.